Implementation of The Project For Strengthening The Profile of Pancasila Students (P5) in Schools - Rediyono Rediyono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study examines issues in implementing the P5 program at State High School 14 Samarinda. Method: The data in this study are interview and observation data with correspondents of 3 teaching staff, three education staff, and five learners from State High School 14 Samarinda. Results: The results show that in its implementation, State High School 14 Samarinda experienced difficulties at the beginning of the project implementation where there were no references from other schools or incomplete explanations from the Office of Education and Culture, both provincial and district, which caused several obstacles, especially in developing children's primary capital. With these limitations, the workforce and education personnel work professionally by collaborating with novice teachers and senior teachers through experiences and joint discussions with parents about their children's essential capital so that they quickly know which ones need improvement. Novelty: Previous studies have analyzed the implementation of individual and organizational programs in education management and have yet to pay attention to the implementation of programs, especially the P5 program. Therefore, this research seeks to introduce the P5 program at the senior high school education level to make learners aware of the importance of cognitive and affective abilities in life, including the problems they face.